Peyresq Lectures on Nonlinear Phenomena, Volume Ii. - Sepulchre, Jacques-Alexandre (World Scientific Publishing Company, 2003)
This book is the second volume of lecture notes on various topics in nonlinear physics delivered by specialists in the field who gave courses in the small village of Peyresq (France) during summer schools (2000, 2001, 2002) organised by the Institut Non Linéaire de Nice (INLN), in collaboration with the Institut de Recherche de Physique Hors Equilibre (IRPHE). The goal is to provide good summaries on the state of the art of some domains in physics having the common denominator of belonging to nonlinear sciences, and to promote the transfer of knowledge between them. Contents: The Dynamo Effect.